Thermal properties of vegetable oils used in lubricants - Jose de Jesus Agustin Flores Cuautle (Discover Chemical Engineering)
Abstract Lubricants are substances that reduce friction and wear, thus reducing the mechanical energy needed to perform movement. Several ways have been used to improve the properties of the oil; one of them is to incorporate additives into the main oil component. Among the additives used to enhance oil properties, vegetable oil additives are chosen because of their renewable properties. Depending on the application, viscosity, degradability time, toxicity, or thermal properties are standard features that are desirable to improve. Given the relationship between the thermal properties and the kinetic viscosity, it is good to know the thermal properties of the sample. Because most of the studies about the thermal behavior of vegetable oils are focused on oil-fuel transformations and left behind thermal diffusivity and effusivity, the present work introduces a compilation of the thermal properties of different vegetable oils used as additives in biolubricants. The selected method to obtain those thermal properties is the photothermal method; because these techniques can be uncommon in several disciplines, a brief description is included. The thermal diffusivity for the reported oils is in $$\:4\:-\:14$$ $$\:×\:{10}^{-8}{m}^{2}{s}^{-1}$$ range, whereas the dynamic viscosity is in the $$\:4\:-15\:cSt$$ range, which provides a wide range for performing modifications over a base fluid.